Analisis Pendapatan Usahatani Tebu (Saccharum Officinarum L.) Tanam dan Kepras Di Kecamatan Kandat - Agustin, Ferica; Winahyu, Nastiti; Fatmawati, Erlin Widya (JURNAL ILMIAH AGRINECA, 2024)
Differences in cultivation techniques cause differences in the use of production factors in sugarcane farming. The aim of this research is to determine the factors used in planting sugar cane and coconut farming and to analyze the level of income from planting sugar cane and coconut farming. The results of the analysis show that the farming business being carried out is profitable. The results of the R/C Ratio analysis for planted sugar cane and palm fruit are 1.13 and 1.38. An R/C Ratio value of more than 1 indicates that the farming business is feasible to run or cultivate.